Innovative Technologies of English Learning - Sharipova Maloxat Saidjanovna (Zien Journals, 2022)
The article analyzes the ways to develop students' linguistic, sociolinguistic, pragmatic and strategic competencies in the teaching of English with the help of innovative technologies within the communicative approach, the methodological support for the use of innovative technologies based on the development of independent learning. Keywords: English, innovation, technology, educational technology, interactive, method
Keywords: Innovation; Organize online teaching; online teaching; online assessment